Swedish Typo-Morphology – Morphological Conceptualizations and Implication for Urban Design - Todor Stojanovski (Iconarp International Journal of Architecture and Planning, 2019)
Typo-morphology is a branch of urban morphology that understands physical form, formation and transformation in cities with use of types and typologies. This paper describes three Swedish typo-morphological approaches and discusses urban morphology and typologies in a context of urban design and planning practices. One approach describes architectural styles and typical buildings for different historical periods. The second focuses on classifying neighborhood types and their physical attributes. The third complements the second and argues that the Swedish neighborhood typology describes not only physical spaces, but also social structure.